(untitled) (Journal of the College of Basic Education, 2024)
This research paper investigates the influence of Task -based method on learning EFL writing composition of second-year intermediate school students at AL-Sediek Intermediate School For Boys, Diyala Governorate, Iraqi Public school. Students who were participated in this study composed of (88) male students distributed equally into two groups, the empirical group and control one, each one has (No.= 44students). The second course of the academic year(2024-2025) was concerned in this research .The empirical group was exposed with the treatment“ Task-Based method” while the control group was taught by regular teaching method. Pre-posttest design was employed. Tools comprised an EFL test-writing ,writing composition and a rubric for evaluating students’ works. The study was continued for eight weeks ,T-test for one and two samples was utilized, the results have shown that the scores of students in the empirical group overpassed the control group on the developing writing skills as a consequence of the teaching Task-based in writing composition. The findings also showed that students of the empirical group in the pre-test of writing skills outperformed those in other group .